Problematizing infrastructural "fixes": critical perspectives on technocratic approaches to Green Infrastructure. Issue 3 (16th March 2023) - Diep, Loan; Parikh, Priti; Dodman, David; Alencar, Juliana; Martins, José Rodolfo Scarati
ABSTRACT : This paper analyzes the concept of Green Infrastructure (GI) in urban context, challenging the extent to which it can support a transition towards more socially inclusive forms of urban governance. It builds on the argument that the false promise of "win-wins" in the conceptualization of urban greening participates in the creation of blind spots in practice. Using the case of São Paulo, we bring attention to techno-managerial patterns within top-down governance structures. A political ecology lens helps to analyze power relations at play in the context of a linear park project implemented in an informal settlement. It reveals how current urban governance structures create barriers to the practice of GI, notably because projects often remain incomplete, but also because participatory processes often remain limited. The practice of GI normalized as a technical-rational endeavor leaves limited space for "non-expert" knowledge. Complex settings where intertwined socio-environmental issues cause conflicts over space demand equally complex efforts that go beyond infrastructural "fixes". To support the institutionalization of GI, a fuller and grounded "translation" process of the concept needs to be supported by forms of urban expertise centered on communities' needs and local dynamics. We argue that only then will GI support the democratization of urban planning.